Biological Pathway Introduction of Quarantine Animal Disease through International Waste at Soekarno Hatta International Airport, Indonesia - Riasari, Julia Rosmaya; Sudarwanto, Mirnawati Bachrun; Indrawati, Agustin; Latif, Hadri; Lukman, Denny Widaya (RA Journal of Applied Research, 2021)
International flights coming to Indonesia, in addition to bringing in passengers, also brings in passenger’s food waste and garbage from the activities in the airplane. Soekarno Hatta International Airport (SHIA), as one of the busiest airports in Indonesia has great potential as a waste producer. International waste has a higher risk in terms of spreading disease to the environment around the airport, which will ultimately impact human and animal health in general. Waste risk assessment carried by international aircraft as a risk carrier of quarantine animal disease entering Indonesia has never been done. The aim of this study was to identify the biological pathway from the entry of pathogens through international waste and how to prevent it. The results, there were three pathways of international waste management at SHIA. The first pathway, the waste was not unloaded from international aircraft and returned to the country of origin. The second pathway, international waste was unloaded from international aircraft, then destroyed in incinerators inside the airport area. The third pathway, the waste was managed by the inflight catering company and taken out of the SHIA. The third pathway has the highest risk as an entry pathway of quarantine animal disease. There was a possibility that food waste was reused as animal feed. Regulations regarding airport waste management exist, but the implementation is not optimal. The authority and agencies related to international waste at SHIA need to enforce the existing rules about international waste management, to prevent the spread of diseases due to waste.